2012
DOI: 10.1111/jace.12000
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Structural Modification of Nanostructured Mesoporous Silicon Oxycarbide Glasses Obtained from Preceramic Hybrids Aged in NH4OH

Abstract: Highly meso‐porous silicon oxycarbide glasses have been obtained from preceramic hybrid materials aged in NH4OH solutions. Surface characterization reveals the amphoteric character of the surface because of the presence of carbon and silica nanodomains. The dependence of the surface Lewis base constant with the concentration of the NH4OH solution suggests different distribution in the carbon nanodomains because of the addition of the aging solution. Structural characterization reports on the increase in the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…They have been obtained through various approaches, including direct blowing, sol-gel processing, sacrificial organosilane linkages, templates, electrohydrodynamic forming, and others [18][19][20][21]. The sol-gel approach is one of the most promising methods for synthesizing porous SiOC ceramics with an average pore size ranging from several micrometers to millimeters.…”
Section: Introductionmentioning
confidence: 99%
“…They have been obtained through various approaches, including direct blowing, sol-gel processing, sacrificial organosilane linkages, templates, electrohydrodynamic forming, and others [18][19][20][21]. The sol-gel approach is one of the most promising methods for synthesizing porous SiOC ceramics with an average pore size ranging from several micrometers to millimeters.…”
Section: Introductionmentioning
confidence: 99%
“…Grossenbacher et al [148] demonstrated that the polymer-derived ceramics were stable and low toxicity, and their electrical conductivity could be adjusted by carbon doping, which could be used in implantable electrode applications such as pacemakers. Tamayo et al [149][150][151] fabricated mesoporous SiOC for controlled drug delivery. A mixture of organosilicon sol was prepared and aged to form gel by the addition of NH 4 OH solution, which transferred into SiOC after pyrolysis at 1100 ℃.…”
Section: Wwwspringercom/journal/40145mentioning
confidence: 99%
“…These bonds are responsible for durability both of xerogels and glass, which is obtained after thermal processing [ 41 ]. It is during the pyrolysis process when the pores are formed, and their size and shape depend mainly on precursors and the type of solvent used in synthesis [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%